(untitled) (Politeja, 2018)
The elections in June 1992 brought to power Vladimir Meciar‘s Movement for Democratic Slovakia (HZDS) in Bratislava and Vaclav Klaus‘ Civic Democratic Party (ODS) in Prague. In the concept of HZDS the idea of a parity (which is impossible to achieve between two units of differing size) gradually came to be associated with the concept of “Slovak sovereignty” and Slovakia’s “international legal subjectivity”, both incompatible with Czechoslovakia’s further existence. Such confederative model brought Czechs nothing but troubles. Subsequently, Prague now lost interest in keeping Slovakia within the Czechoslovak state. The result was “the velvet divorce” of Czechoslovakia on 31 December 1992.